ON THE OPERATIVE METHOD MEASURING OF THE ATMOSPHERE’S INFRARED TRANSPARENCY - Asatryan, R. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
The results on development of an original method of atmosphere’s transparency determination in the infrared region are presented. The method is a halfempirical and based on the direct nephelometric and meteorological measurements of the atmosphere’s transparency in the visual region (on λ = 0.55 μ ) with following recalculation to the other spectrum region in diapason from 1 μ to 14 μ . The proposed method provides the possibility of the operative valuation “optical weather” in the atmosphere, especially in full-scale tests thermovision equipment and devices of night vision.